DEVELOPMENT OF EFFECTIVE USE OF LAND AREAS IN ECONOMIC ZONES IN G'IJDUVON DISTRICT - G. I.Rajabova; M. F. Aminjonov; Sh.F. Murtazoyev; A. R. Idiboyev (Web of Journals Publishing, 2025)
This article explores the current state and future prospects of efficient land use in the economic zones of the G'ijduvon district. It provides information on the geosocial location of the district, land resource distribution, and economic zones. Additionally, the article analyzes challenges related to the efficient use of land, such as land degradation, water resource distribution, and unclear land allocation. The article suggests the implementation of modern technologies and methods, such as Geographic Information Systems (GIS), digital maps, and sustainable management practices in agriculture, to enhance land use efficiency. Based on the proposed recommendations, strategic approaches are developed for the development of the district's economic zones and the effective use of land resources. The article aims to improve the land resource management system in the G'ijduvon district and ensure sustainable development.
Keywords: G'ijduvon district, economic zones, land resources, efficient use, GIS, cadastre, land planning, ecological issues, water resources, land degradation, digital maps, land management.